ANALISIS PENGARUH PENGAWASAN INTERN, KUALITAS SUMBER DAYA MANUSIA, DAN PENERAPAN AKRUAL BASIS TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH PROVINSI PAPUA - Maniani, Onis; Allo Layuk, Paulus K; Falah, Syaikhul (Universitas Cenderawasih, 2022)
The purpose of this research is to; 1) Analyzing the influence of internal control, the quality of human resources and the application of the accrual basis simultaneously on the quality of the Papuan Provincial Government's financial reports. 2) Analyzing the influence of internal control, the quality of human resources and the application of the accrual basis partially on the quality of the Papuan Provincial Government's financial reports, 3) Analyzing the influence of variables that have a dominant influence on the quality of the Papuan Provincial Government's financial reports.The method used in this research is multiple regression analysis. Where this analysis method is a statistical method used to test the relationship between several independent variables to one dependent variable.The results of the analysis show that, internal control, quality of human resources and the application of the accrual basis simultaneously affect the quality of regional financial reports in Papua Province. This means that the higher the internal control, the quality of human resources and the application of the accrual basis can be understood and implemented properly, the quality of the local government financial reports produced will be better. On the other hand, if the internal control, quality of human resources and the application of the accrual basis do not meet accounting policies, it can lead to poor quality of local government financial reports. Internal control, quality of human resources and the application of the accrual basis partially affect the quality of regional financial reports in Papua Province. This means that, if internal control is carried out properly, the quality of the financial reports produced will increase, as well as the quality of human resources and the application of the accrual basis. The variable quality of human resources has a dominant influence on the quality of regional financial reports in Papua Province. With the existence of human resources who have competence, especially in the field of accounting or finance, it will be able to encourage the realization of the presentation of quality government financial reports so as to increase the accuracy and accountability of local government financial management.Â